Vida JESENŠEK, 2021: Beiträge zur deutschen und slowenischen Phraseologie und Parömiologie.: University of Maribor Press. (International Book Collection Zora, 142). 248 p. - Fabčič, Melanija Larisa (Slavia Centralis, 2022)
In 2021, a monograph by Vida Jesenšek entitled Beiträge zur deutschen und slowenischen Phraseologie und Parömiologie (Contributions to German and Slovenian phraseology and paremiology) was published by the University of Maribor Press (as part of the Zora international book collection).